Numerical investigation of concrete filled hollow precast composite columns subjected to lateral cyclic loading - Paudel, Satish; Tanapornraweekit, Ganchai; Tangtermsirikul, Somnuk (Engineering structures, 2022)
•Investigation of monolithic and composite columns under cyclic loads was performed.•Concrete models were investigated to simulate RC structures under cyclic loadings.•Contact algorithm used to model composite columns under cyclic loading was verified.•The FE model can capture responses of the composite columns under cyclic loadings.•Influence of thickness and strength of precast plate and rebar details was studied.•Methods to enhance ductility of composite columns under cyclic loads are provided. This paper describes a numerical study performed to investigate the behaviour of concrete infilled hollow precast composite columns (HPCC) subjected to lateral cyclic loading. Finite element analysis of monolithic (RC) and composite (HPCC1 and HPCC2) columns are performed and the results thus obtained are compared with documented experimental results. The present study focuses on the capability of numerical codes to capture the behaviour of the columns, such as load–displacement relationship, softening and failure modes under cyclic loading. To capture the performance of tested composite columns, a study was first performed to select a suitable material model that can further be considered appropriate to depict the cyclic performance of reinforced concrete (RC) structures. Moreover, the investigation was performed to model two concrete surfaces (precast and cast-in-situ) in contact through a contact algorithm for a precast encased composite column. Finally, a study on interface shear stress transfer mechanism and effects of confinement provided by the encasement to the inner core was performed for HPCC1 and HPCC2 composite columns. After performing numerical study and comparing with the obtained test results, a continuous surface cap material model (MAT 159) available in LS-DYNA FE code was observed to be suitable to model concrete for analyzing the behavior of RC structures subjected to lateral cyclic loading. Moreover, to simulate the behaviour of composite structures, the use of a tiebreak contact algorithm is suggested. It was observed that due to the presence of cross-ties penetrating into the inner core of HPCC1, the composite action between the inner core and outer precast encasement was enhanced, with delayed damage in the outer encasement. However, in composite column HPCC2, the ties did not penetrate into the inner column core, so interface shear strength, resulted only from cohesion and friction, caused severe damage in the outer encasement at ultimate load. The presence of a single tie and smaller thickness of precast encasement in HPCC1 resulted in lower displacement ductility of HPCC1 compared to composite column HPCC2. Moreover, parametric studies were performed to elucidate the influence of the thickness of the precast plate and reinforcement arrangement to enhance the ductility of the composite columns through a series of numerical analyses of the modified columns.